Möjligheternas skolgård : om att skapa förutsättningar för en välanvänd utemiljö - exempel från Luleå - Johansson, Malena (SLU/Dept. of Urban and Rural Development, 2007)
Children's need of a good environment of playing outdoor at schoolyards is, both from a perspective of commonly public's health and from the children themselves, indisputable. Children who have a good and varying playground develop physically, psychologically and socially. As an instrument of pedagogic a playground also is valuable for example in teaching the round, periodical successions and understanding of democratic processes. The conception playground means here in my work the environment outdoor for children at schools up to about twelve years old. What is a good playground then? How is it possible for a landscape architect to contribute improvements? The purpose of my work has been to enlarge my knowledge about playgrounds, understand more of the profession as a landscape architect and apply a perspective of children in the planning. To sum up, the shaping of playgrounds has great importance for the activities of the children and if the teachers make use of it, the teaching. A good playground gives the delight, the excitement and the curiosity free spaces and stimulates new challenges. There are places where the children are free to play as they want. Natural environments with its variableness and rich content of loose parts have a certain importance in playing. And as these places are not beforehand decided for specified activities the children are free to create their own spaces and that is a central meaning of how children experience their outdoor environment. A broad offer of places is important but to create a landscape of playing you also need to find something which will keep the different functions together. Stones, water, sand and soil are elements which give many different use as well as vegetation and differences of height. Other important aspects of a good playground are accessible entrance and freedom from traffic of vehicles. At the same time as I have studied literature, consulted the staff of the school, administrators and those who are responsible of looking after the playgrounds, I have ...